Linking long non-coding RNAs and SWI/SNF complexes to chromatin remodeling in cancer. Issue 1 (December 2017) - Tang, Yanyan; Wang, Jinpeng; Lian, Yu; Fan, Chunmei; Zhang, Ping; Wu, Yingfen; Li, Xiayu; Xiong, Fang; Li, Xiaoling; Li, Guiyuan; Xiong, Wei; Zeng, Zhaoyang
Abstract Chromatin remodeling controls gene expression and signaling pathway activation, and aberrant chromatin structure and gene dysregulation are primary characteristics of human cancer progression. Recent reports have shown that long non-coding RNAs (lncRNAs) are tightly associated with chromatin remodeling. In this review, we focused on important chromatin remodelers called the switching defective/sucrose nonfermenting (SWI/SNF) complexes, which use the energy of ATP hydrolysis to control gene transcription by altering chromatin structure. We summarize a link between lncRNAs and the SWI/SNF complexes and their role in chromatin remodeling and gene expression regulation in cancer, thereby providing systematic information and a better understanding of carcinogenesis.